Tissue-specific activation of gene expression by the Synergistic Activation Mediator (SAM) CRISPRa system in mice - Charleen Hunt (Nature Portfolio, 2021)
CRISPR-Cas9 is a gene editing tool that can be used to modulate gene expression. Here, the authors report the generation of a mouse model that express all components of the CRISPR-Cas9 guide directed Synergistic Activation Mediator (SAM), demonstrate that gene activation can be achieved with various delivery methods and include generation of a disease model of hypercholesterolemia